1996
DOI: 10.1074/jbc.271.19.11214
|View full text |Cite
|
Sign up to set email alerts
|

Evidence That Syntaxin 1A Is Involved in Storage in the Secretory Pathway

Abstract: Syntaxin 1A is a nervous system-specific protein thought to function during the late steps of the regulated secretory pathway by mediating the docking of secretory vesicles with the plasma membrane. We have examined the effects of transiently overexpressing syntaxin 1A on protein secretion in constitutively secreting cell lines that do not normally express the protein. Syntaxin 1A showed the constitutive release of marker proteins human growth hormone (hGH) and vesicular stomatitis virus glycoprotein from COS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
78
1

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(91 citation statements)
references
References 47 publications
(49 reference statements)
12
78
1
Order By: Relevance
“…1, GppNHp stimulates catecholamine release above basal levels in the absence of added Ca 2+ with 5 mM EGTA present. This Ca2+-independent secretion triggered by GppNHp, as in previous work [33,34], is smaller than that triggered by 10 BM Ca 2+ but was reproducibly observed. The release due to GppNHp was 2.5 _+ 0.2% of total cellular catecholamine above basal from 17 cell batches.…”
Section: Resultssupporting
confidence: 63%
See 3 more Smart Citations
“…1, GppNHp stimulates catecholamine release above basal levels in the absence of added Ca 2+ with 5 mM EGTA present. This Ca2+-independent secretion triggered by GppNHp, as in previous work [33,34], is smaller than that triggered by 10 BM Ca 2+ but was reproducibly observed. The release due to GppNHp was 2.5 _+ 0.2% of total cellular catecholamine above basal from 17 cell batches.…”
Section: Resultssupporting
confidence: 63%
“…Various GTP analogues have multiple effects on secretion from permeabilised chromaffin cells [47] which includes stimulation of release from permeabilised cells [33][34][35] and exocytosis in patch-clamped cells [36] by GppNHp at very low free Ca 2+ concentrations. Like Ca2+-induced secretion, Ca2+-independent catecholamine release stimulated by GppNHp is partially MgATP-dependent, is substantially inhibited by prior treatment with botulinum neurotoxin D and is partially inhibited by neurotoxins C1 and E. These results suggest that both activators of exocytosis activate a common mechanism leading to exocytosis that requires the SNARE proteins, VAMP, syntaxin and SNAP-25 and would argue against the presence of a SNARE-independent pathway for exocytosis in adrenal chromaffin cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Catecholamine release from adrenal chromaffin cells, vasopressin release from neurohypophysial terminals and insulin release from pancreatic 13 cells is inhibited by botulinum neurotoxin A [14][15][16][17][18]. However, the variable cleavage of SNAP-25 in pancreatic [3 cells, the incomplete inhibition of vasopressin and catecholamine release and the preferential attack of ATP-dependent priming by botulinum neurotoxin A suggested that this toxin may have molecular targets of different sensitivities [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%